Tanmiyah Mahârah al-Kalâm bi Tathbîqi at-Tharîqah al-Ittishâliyyah: al-Bahts at-Tanfîdziy fî al-Fiah ad-Dirâsiyyah - Afif Amrullah (IAIN Madura, 2021)
This research was intended to improve student's speaking ability by applying communicative method, and at the same time, to find out the effectiveness of using this teaching method in promoting speaking skills. The problem with this research was formulated interrogatively as follows: Is the implementation of communicative methods capable of improving the speaking skills of eighth grade students at National Islamic Junior School, Bandar Lampung? This research can be categorized as Classroom Action Research, and as subject research. They are all eight grade students at National Islamic Junior School Bandar Lampung. To obtain data, this research used several methods: observation, interview, documentation, and testing. This research is qualitative research, and the data was analyzed in three steps: data reduction, data display, and then interpretation. This research results in the following conclusions: In first session, the students who passed the test 54.40% and who failed 45.59%, in second session, students who passed the test 86.64%, and who failed 13.35%, and in the third session the students who passed test 78.83%, and who failed 21.16%, than can be concluded that implementing a communicative method in teaching Arabic as a second language is capable of improving speaking skills.